Utilization of Automation Studio Software to Improve the Creative Thinking Abilities of Electrical Engineering Students in Designing Electropneumatic Circuits - Endryansyah, Endryansyah; Suprianto, Bambang; Rusimamto, Puput Wanarti; Anifah, Lilik; Wardhono, Arie (Journal of Engineering Education Transformations, 2025)
This study aimed to analyze the impact of using Automation Studio software to enhance the creative thinking skills of electrical engineering students in designing electropneumatic control systems. Creative thinking is a critical skill for electrical engineering students, particularly in the design of electropneumatic systems. Automation Studio serves as a tool that facilitates the development of these skills by providing a practical platform for circuit design and simulation. The study employed a quasi-experimental design with a pretest-posttest control group. A total of 23 fifth-semester electrical engineering students participated in this study. Data were collected through tests and performance evaluations of students' design skills. The results indicated a significant improvement in students' creative thinking skills. Learning outcomes increased by 30%, from a pre-test score of 67.5 to a post-test score of 87.5. Additionally, design skills improved by 34.9%, with scores rising from 65.5 to 88.33. These findings suggest that Automation Studio can effectively enhance students' creative abilities in designing electropneumatic control systems. This study highlights the potential of Automation Studio as a teaching tool in engineering education to foster creativity in system design. It provides valuable insights for educators seeking to integrate simulation software into their curriculum to improve their design and problem-solving skills. This research contributes to the limited body of knowledge on the application of Automation Studio in developing creative thinking skills among electrical engineering students, particularly in the context of electropneumatic system design.